2019
DOI: 10.1371/journal.pone.0219118
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition support for HIV-TB co-infected adults in Senegal, West Africa: A randomized pilot implementation study

Abstract: Background Food insecurity can contribute to poor adherence to both tuberculosis treatment and HIV antiretroviral therapy (ART). Interventions that target food insecurity have the potential to increase treatment adherence, improve clinical outcomes, and decrease mortality. The goals of this study were to compare the feasibility, acceptability, and potential impact of implementing two different forms of nutrition support for HIV-TB co-infected adults in the Casamance region of Senegal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In Senegal, PLWTB who received deliveries of food baskets and ready-to-use therapeutic foods which cost less than a dollar a day achieved 95% adherence to both antiretroviral and antimycobacterial therapy as well as reduction in food insecurity and improvement in nutritional status. 45 In India, PLWTB who received nutritional supplementation that cost $10 per month were less likely to disengage with care than those who did not receive supplementation. Only one person (1%) was lost to follow up in the supplementation arm as compared to 41 individuals (10%) in the no supplementation arm.…”
Section: Tb Treatmentmentioning
confidence: 99%
“…In Senegal, PLWTB who received deliveries of food baskets and ready-to-use therapeutic foods which cost less than a dollar a day achieved 95% adherence to both antiretroviral and antimycobacterial therapy as well as reduction in food insecurity and improvement in nutritional status. 45 In India, PLWTB who received nutritional supplementation that cost $10 per month were less likely to disengage with care than those who did not receive supplementation. Only one person (1%) was lost to follow up in the supplementation arm as compared to 41 individuals (10%) in the no supplementation arm.…”
Section: Tb Treatmentmentioning
confidence: 99%
“…A study among HIV-TB coinfected patients in Senegal reported that 41.6% of the participants felt that the taste could be improved; 16.6% felt it was too salty, 16.6% felt it was both too salty and too sweet, while 8.3% felt it was too sweet. 4 The adherence to peanut-based EDNS in this study was 100%. However, the study was constrained by very low sample size.…”
Section: Discussionmentioning
confidence: 58%
“…Studies have shown that incentives such as nutritional supplementation increases adherence to the antituberculosis treatment, 4,15 and this strategy can be used to decrease default rates and improve adherence in our settings. India has set a target to eliminate tuberculosis by the year 2025.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations